Changing equal opportunities in transition? : gender and equal opportunities in Kiruna, Sweden - King, Allen Douglas; Barry, Jim; Berg, Elisabeth (Luleå tekniska universitet, Arbetsvetenskap, 2008)
This paper considers the effects on the local labour market, for both women and men, of the relocation of Kiruna, a large town in the north of Sweden. Whilst the area of Kiruna has been dominated by mining activity for many years this has now become the source of both problems and opportunities for those in the labour market, if not the whole community, as they ready themselves for the relocation of their town - presently situated above a number of deep mine shafts - to a safer area. Mining, transport and engineering industries flourish in Kiruna, with the current labour market and the relocation of the town expected to generate growth and a regional expansion. But the labour market for mining has been dominated traditionally by men, with women found predominantly in the public sector. A question that rises is how much will change, and who might be winners and losers, when the town relocates? Equal opportunities in labour markets have long been a part of political and philosophical debates in a number of European countries, not least Sweden where achievements of political gender equality debates have earned it an international reputation as a world leader in gender equality (Regeringskansliet, 2007). Indeed, in Sweden equal opportunities in respect of gender have been promoted as a part of the school curriculum since 1970 (SCB, 2006; Regeringskansliet, 2007). Subsequent to this and other achievements during the 1970's, social democratic politicians and other campaigners have striven to keep equal opportunities at the forefront of social awareness. This remained the case throughout the 1980's and 1990's, and into the new millennium (SCB, 2006). In 2004, for example, strategies for the integration of gender equality in Government Offices in Sweden were implemented, followed by "new" gender equality policies, that also focused on equal opportunities, in 2006 (SCB, 2006). However, in 2007 a "new" liberal approach to gender equality emerged, its significance albeit somewhat unclear. It is this on which the study ...